Plasmonic‐Based Mechanochromic Microcapsules as Strain Sensors. Issue 39 (21st August 2017) - Burel, Céline. A. S.; Alsayed, Ahmed; Malassis, Ludivine; Murray, Christopher B.; Donnio, Bertrand; Dreyfus, Rémi
Abstract: Efficiently detecting mechanical deformations within materials is critical in a wide range of devices, from micro‐electromechanical systems to larger structures in the aerospace industry. This communication reports the fabrication of new mechanochromic micrometer‐size capsules enabling the detection of strains. These microcapsules are synthesized using an emulsification approach. They are made of densely packed gold nanoparticles embedded in a spherical silica crust. Billions of these composite spherical microcapsules are fabricated in a single batch. Each microcapsule is an opto‐mechanosensor by itself, and can easily be recovered and incorporated into polymer films. When the films are stretched, the microcapsules are deformed into elongated ellipsoidal shapes and the distance between the Au NPs embedded in their shells concomitantly increases. As the extinction of Au NPs depends on the separation between the Au NPs, microcapsules exhibit different colors when they are elongated. These novel sensitive microcapsules can be used to detect and measure strain in polymer films by outputting color information. Abstract : Mechanochromic gold–silica microcapsules are used as optical sensors to detect mechanical deformations. Densely packed gold nanoparticles (NPs) are embedded in a spherical silica crust, forming a microcapsule. The strain of the microcapsule changes the distance between the NPs. As the NPs extinction depends on the separation between the NPs, microcapsules exhibit different colors whether they are elongated or not.